Intermittent Bi-Daily Sub-cutaneous Teriparatide Administration in Children With Hypoparathyroidism: A Single-Center Experience - Bernardor, Julie; Flammier, Sacha; Cabet, Sara; Lemoine, Sandrine; Chapurlat, Roland; Molin, Arnaud; Bertholet-Thomas, Aurélia; Bacchetta, Justine (Frontiers in Pediatrics, 2021)
Introduction The use of teriparatide has been reported in children with hypoparathyroidism as second-line off-label therapy. Methods We aimed to retrospectively report our pediatric experience of bi-daily sub-cutaneous teriparatide. Results are presented as median (25th-75th quartile). Results At a median age of 10.7(8.1-12.6) years, an estimated glomerular filtration rate (eGFR) of 110(95-118) mL/min/1.73m², calcium levels of 1.87(1.81-1.96) mmol/L and an age-standardized phosphate of 3.8(2.5-4.9) SDS, teriparatide therapy was introduced in 10 patients at the dose of 1.1(0.7-1.5) µg/kg/day (20µg twice daily), with further adjustment depending on calcium levels. Six patients already displayed nephrocalcinosis. Severe side effects were reported in one child: two episodes of symptomatic hypocalcemia and one of iatrogenic hypercalcemia; one teenager displayed dysgueusia. Calcium levels at H0 did not significantly increase whilst calcium at H4 and phosphate levels significantly increased and decreased, respectively. After 12 months, eGFR, calcium and age-standardized phosphate levels were 108 (90-122) mL/min/1.73m², 2.36(2.23-2.48) mmol/L, 0.5(-0.1;1.5) and 68(63-74) nmol/L, respectively, with a significant decrease in phosphate levels (p=0.01). Urinary calcium and calcium/creatinine ratio remained stable; no nephrolithiasis was observed but two moderate nephrocalcinoses appeared. Conclusion Intermittent teriparatide therapy significantly improves calcium an phosphate control, without increasing calciuria. It appears to be safe and well-tolerated in children.